Carnivore activity at Klasies River Mouth: a response to Binford - Thackeray, J Francis (Bernard Price Institute for Palaeontological Research, 1990)
Environmental and behavioural factors contributed to variability in the relative abundance of Raphicerus (grysbok/steenbok) represented in Late Pleistocene and Holocene deposits at the complex of caves at Klasies River Mouth and at Nelson Bay Cave in the southern Cape Province, South Africa. Binford has used the relative abundance of Raphicerus in an index assumed to measure the degree of hunting by Middle Stone Age hominids. However, the occurrence of relatively high numbers of Raphicerus with leopards and baboons in some layers is likely to have been associated, at least in part, with leopard activity, particularly at times when relatively large ungulates were not common in the palaeoenvironment and when the cave sites were not frequently occupied by hominids with control over fire. Binford's indices are re-assessed in the light of other indices which are designed to identify assemblages that have a relatively high probability of having been accumulated by leopards and/or other carnivores.
Keywords: Raphicerus; Pleistocene; Holocene; taphonomy; hominid